Dampak Konflik Keluarga Terhadap Kesejahteraan Psikologis Anak Prasekolah - Sabrina Ais Zahra; Sofiatun Aniisa; Rahmi Anekasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Family conflict is a fairly common phenomenon that can affect children’s lives, particularly in mental and emotional aspects. This study aims to identify the causes of family conflict, its impact on young children, and the role of the Child Protection Agency in assisting with its management. This study employs a qualitative method using a literature review approach sourced from various books and scientific journals. The findings indicate that family conflicts can be triggered by ineffective communication, differing perspectives, economic issues, and the involvement of third parties. Ongoing conflicts can cause children to feel insecure, experience anxiety, suffer from reduced self-confidence, and face difficulties in social interaction. Furthermore, a dysfunctional family environment also influences the process of a child’s personality development from an early age. In this context, the Child Protection Agency plays a crucial role in providing guidance, protection, and support for the child’s psychological recovery. However, its implementation still faces various challenges, necessitating collaboration among various stakeholders to support children’s well-being.